Serum procalcitonin levels can be used to differentiate between inflammatory and non-inflammatory diarrhea in acute infectious diarrhea. Issue 32 (August 2018) - Shin, Hae Jin; Kang, Sun Hyung; Moon, Hee Seok; Sung, Jae Kyu; Jeong, Hyun Yong; Kim, Ju Seok; Joo, Jong Seok; Lee, Eaum Seok; Kim, Seok Hyun; Lee, Byung Seok
Abstract : Abstract: In this study, we assess the possibility of using procalcitonin levels to differentiate between inflammatory diarrhea and non-inflammatory diarrhea in acute infectious diarrhea. We reviewed the records of 1176 patients who had symptoms of diarrhea, fever (≥37.8 °C), and abdominal pain between March 2011 and May 2015. After applying exclusion criteria, a sample of 514 patients was considered for study. The patient sample was divided into Group A and Group B for inflammatory diarrhea and non-inflammatory diarrhea, respectively. The assessment involved comparing the laboratory characteristics with the clinical characteristics of the groups. The characteristics of Group A, such as white blood cell (WBC), C-reactive protein (CRP), absolute neutrophil count (ANC), and procalcitonin levels, were relatively higher than those of Group B ( P  < .001 for Group A). A receiver operator characteristic (ROC) analysis revealed that the highest area-under-the-curve (AUC) value of procalcitonin (0.797; 95% confidence interval [CI] [0.760, 0.831]; P  < .001), could be used to differentiate between the 2 groups. Procalcitonin exhibited a sensitivity and a specificity of 87.03% and 68.75%, respectively, at a 0.08 ng/mL cut-off level. Procalcitonin was a good candidate biomarker of inflammatory diarrhea than other inflammatory markers.